Back to Course

JSS3: MATHEMATICS - 1ST TERM

0% Complete
0/0 Steps
  1. Binary Number System I | Week 1
    5Topics
    |
    1 Quiz
  2. Binary Number System II | Week 2
    6Topics
    |
    1 Quiz
  3. Word Problems I | Week 3
    4Topics
    |
    1 Quiz
  4. Word Problems with Fractions II | Week 4
    1Topic
    |
    1 Quiz
  5. Factorisation I | Week 5
    4Topics
    |
    1 Quiz
  6. Factorisation II | Week 6
    3Topics
    |
    1 Quiz
  7. Factorisation III | Week 7
    3Topics
    |
    1 Quiz
  8. Substitution & Change of Subject of Formulae | Week 8
    2Topics
    |
    1 Quiz
  9. Simple Equations Involving Fractions | Week 9
    3Topics
    |
    1 Quiz
  10. Word Problems | Week 10
    1Topic
    |
    1 Quiz
Lesson Progress
0% Complete

Recall that a quadratic expression has 2 as its highest power.

A quadratic expression is also known as a polynomial of the second degree.

The general form of a quadratic expression is

\( \scriptsize ax^2 + bx + c \)

 Where (a ≠ 0)

a is not equal to zero.

where a, b and c represent any number 

a is called the coefficient of  x

b is called the coefficient of x 

c is a constant term.

Example

Write down the coefficient of x2x, and the constant in the following expressions.

a. x + 3x + 1

\( \scriptsize ax^2 + bx + c \) compare coefficients

a = 1, b = 3, c = 1

b. 2x– 8

\( \scriptsize ax^2 + bx + c \) compare coefficients

We can see that we only have a and c after comparing coefficients.

a = 2 and c = – 8

c. 7xx – 2

\( \scriptsize ax^2 + bx + c \) compare coefficients

a = 7,  b =  -1,    c =  -2

d. 4x– 6x + 4

\( \scriptsize ax^2 + bx + c \) compare coefficients

 a = 4,   b = -6,   c =  4

e. (x – 1)(x – 2)

= x(x – 2) -1(x – 2)

= x2 – 2xx + 2

= x2 – 3x + 2

\( \scriptsize ax^2 + bx + c \) compare coefficients

a = 1,   b = -3,   c = 2

back-to-top
error: